O ensino de filosofia no ensino médio técnico - Vandresen, Daniel Salésio (Editora Oficina Universitária, 2023)
In this book, we argue that the ethical-political task of teaching philosophy in technical secondary education is to provide learning to exercise oneself through a philosophical practice that takes place in an agonistic tension of cohabiting problems. In this work we seek to reflect on the teaching of philosophy as an existential practice, this because, traditionally, the teaching of philosophy has been analyzed from the point of view of the pedagogical processes “what to teach?” (reflection on contents) and “how to teach philosophy?” (reflection on methodologies), however, our proposal is to shift teaching-learning issues to think of philosophy and its teaching as an attitude (philosophical ethos), that is, as an exercise of the self that transforms life. And in this exercise about life as the creation of unique experiences and peculiar attitudes, philosophy plays an indispensable role in the formation of an education for difference, confronting the current scenario of growth of prejudiced behavior and spaces of intolerance.